Inclusive Approaches in Future Health Policy: Ethical Challenges of Using Artificial Intelligence in Medicine - Hassan Al-Mutawa; Fatima Al-Mazrouei (Journal of World Future Medicine, Health and Nursing, 2025)
The rapid integration of artificial intelligence in medicine has sparked significant advancements in patient care, diagnostics, and treatment planning. However, as artificial intelligence technologies become increasingly prevalent in healthcare, they raise complex ethical challenges that must be addressed to ensure their responsible use. These challenges include concerns about data privacy, algorithmic bias, accountability, and the potential for unequal access to artificial intelligence-based medical interventions. This study explores the ethical implications of using artificial intelligence in medicine and proposes inclusive approaches for future health policy. A qualitative research methodology was employed, including expert interviews and policy document analysis, to examine the ethical issues surrounding artificial intelligence integration in medical practice. The findings indicate that while artificial intelligence holds great promise for improving healthcare efficiency and accuracy, its implementation must be accompanied by robust regulatory frameworks that prioritize equity, inclusivity, and accountability. The study emphasizes the need for collaborative policy-making involving stakeholders from various sectors to ensure that artificial intelligence technologies are developed and deployed in ways that benefit all populations, particularly marginalized communities. The research concludes that inclusive approaches to artificial intelligence integration in healthcare policy can help mitigate ethical risks and foster a healthcare system that is both innovative and ethically sound.